Study of Possible Obstacles Preventing Obtaining a Tokomak Regime in the Egyptian Machine. (21st July 2010) - Hegazy, H.; Diab, F.; Abd El-Aziz, K.; Gott, Yu. V.; Dremin, M. M.
Abstract : The main goal of this study is to clarify the possibility to obtain the plasma discharge and to prolong its duration as much as possible, and to analyze what are the preventing reasons of obtaining this goal. Possible reasons can be improper operation of the power supply system, a high level of stray magnetic fields, lack of equilibrium, influence of MHD instabilities, and a high level of impurities. We analyze experimentally these possibilities and discuss them in more details.